Statistical analysis of the content of metals in blood serum and in the alternative material in head and neck carcinoma - Małgorzata Herman; Małgorzata Jakubowska; Wojciech Piekoszewski; Anna Woźniak; Agnieszka Przybyłowicz; Marta Szukalska; Ewelina Golusińska-Kardach; Wojciech Gawęcki; Agata Czarnywojtek; Stanisław Walas; Wojciech Golusiński; Marek Ruchała; et al. (Arabian Journal of Chemistry, 2024)
The study attempted to demonstrate the differences in the content of essential and toxic metals in the blood serum and in the alternative material (hair and nails) in patients with head and neck cancer compared to healthy people. Selected metals were determined in the test material with the ICP MS technique. The obtained results were subjected to statistical analysis. The Kolmogorov-Smirnov test was used to verify the hypothesis that each tested chemical compound taken from other tissue affects the possibility of developing head and neck cancer or is an indicator of the disease. All variables (n = 30) were evaluated to verify significant differences (p < 0.05) in each mean between healthy (n = 55) and cancer groups (n = 68). The data matrix was pre-standardized prior to the analyzes due to large differences in the mean of the compounds tested. The unsupervised learning methods were used and supervised learning methods. On the basis of the statistical analysis, the usefulness of the analysis of alternative material was demonstrated in the potential identification of changes caused in people with cancerous changes at a time when they are not yet visible in the blood serum and can be used as a supplementary test in the diagnosis of head and neck cancer. This is particularly important at early cancer as usually laryngeal cancer is diagnosed in advanced stage.